The Yield of Amnioinfusion in the Prevention of Postpartum Hemorrhage - Zloto, Keren; Sivan, Eyal; Yoeli-Ullman, Rakefet; Mazaki-Tovi, Shali; Chauhan, Suneet P.; Bartal, Michal Fishel (American Journal of Perinatology, 2025)
Although amnioinfusion decreases the rate of uterine atony, its effect on postpartum hemorrhage (PPH) is uncertain. This study aimed to assess whether amnioinfusion reduces the risk of PPH in laboring individuals.A retrospective study of all laboring singletons at a tertiary center between January 2013 and December 2022 at ≥34 weeks. Individuals with known major fetal anomalies, stillbirths, or missing delivery records were excluded. The primary outcome was PPH. Neonatal and secondary maternal outcomes were also explored. Adjusted odds ratios (aOR) were estimated using multivariable regression models.Out of 113,816 deliveries during the study period, 83,152 (77.1%) met inclusion criteria, and among them 4,597 (4.03%) had amnioinfusion. Laboring individuals with amnioinfusion were more commonly nulliparous, had more polyhydramnios, oligohydramnios, preeclampsia, gestational diabetes, and fetal growth restriction. Furthermore, individuals with amnioinfusion had a higher rate of labor induction (54.54 vs. 27.8%; p < 0.01) and a higher cesarean rate (36.9 vs. 9.5%; p < 0.01). Following multivariable regression, there was no significant difference in the rate of PPH among individuals who had an amnioinfusion (2.6%) versus those who did not (3.1%; aOR: 0.95, 95% confidence interval [CI]: 0.87, 1.27). The rates of endometritis (aOR: 1.4; 95% CI: 1.04–1.89) and postpartum fever (aOR: 1.70; 95% CI: 1.36–2.12) were higher in those who had amnioinfusion compared with those that did not.Among laboring individuals ≥ 34 weeks, intrapartum amnioinfusion was not associated with a reduction in the rate of PPH and was associated with a higher likelihood of infectious morbidity.
Keywords: amnioinfusion; postpartum hemorrhage; endometritis; postpartum fever